Enhanced Arsenic Removal from Aqueous Solution by Fe/Mn-C Layered Double Hydroxide Composite - Yaru Wang; Yingying Gao; Zongqiang Zhu; Lihao Zhang; Ningning Zhao; Yali Fang; Yinian Zhu; Guifeng Liu (Adsorption Science & Technology)
A novel material named Fe/Mn-C layered double hydroxide composite (Fe/Mn-C-LDH) was synthesized to remove arsenic from an aqueous solution. The removal performance of the composite toward arsenic ions was studied through the batch experiments. The experiment results showed that Fe/Mn-C-LDH exhibited a high adsorption capacity of 46.47 mg/g for As(III) and 37.84 mg/g for As(V) at 318 K, respectively. In addition, the investigation of the release of Fe3+ and Mn2+ in the process of arsenic adsorption revealed that the Fe/Mn-C-LDH exhibited better stability than Fe/Mn-layer double hydroxide (Fe/Mn-LDH) with fewer Mn2+ and Fe3+ releasing under the same condition. The BET results showed that the specific surface area of Fe/Mn-C-LDH decreased after adsorption of As (III) and As (V). Furthermore, the Density Functional Theory (DFT) calculation results proved that the adsorbent combining arsenic by T-site to produce a better adsorption effect for arsenic. Possessing better stability and adsorption capacity, Fe/Mn-C-LDH could potentially serve as a perfect adsorbent for arsenic removal from an aqueous environment. It would provide a promising approach for removing heavy metal from the aquatic environment in the future.